Computation of human health risk in surface water in Ado-Odo Ota, Ogun State, Nigeria - Samuel, Ogbiye A.; Theophilus, Tenebe I.; Praise God, Emenike C.; Winifred, Anake U. (Elsevier, 2018)
Heavy metals find their way into surface and groundwater due to degrading environmental conditions, and as such consistent monitoring to avoid the adverse health implications associated with the consumption of polluted water is required. This study examined the concentrations for Lead (Pb), Nickel (Ni), Zinc (Zn), Chromium (Cr), Cadmium (Cd), Copper (Cu) and Arsenic (As) in the Surface water of River Balogun in Ota, Ogun State, Nigeria during the wet season and estimated the human health risk resulting from prolonged consumption by children and adult of dissimilar age groups without treatment. Although there were persistent occurrence of Nickel (Ni), Copper (Cu), Zinc (Zn) and Arsenic (As) in all stations sampled, the health risk assessment conducted revealed that both population groups are more likely to be affected by high concentration levels of Arsenic than any other Heavy metal present.